Gender Mainstreaming and Technology Application: An Appraisal of TANWA Project (Indian Journal of Extension Education, 2015)
The project “Tamil Nadu Women in Agriculture” (TANWA) was launched in 1986 aimed at technological empowerment of farm women. An impact study was conducted in 2013 to understand the technology application and gender empowerment in Kancheepuram district of Tamil Nadu after more than 10 years of project termination. TANWAbuilt up an effective system for the training of farm women with help of specially recruited female extension staff. Farm women groups widened the scope of their work by taking up savings and other income generating activities. The trained farm women adopted a range of agricultural skills leading to increase the yields of main crops, greater marketable surplus and savings on chemical fertilizers. The influence of women in farm matters goes more or less hand in hand with an increase in their influence over family matters. The project had brought a good degree of gender sensitization at household level while building women’s capacities as skillful and self-confident farmers. The formation of farm women groups had contributed greatly to the continued viability of some of the income generating activities as well as providing a forum for learning, innovating and extending mutual support among them. Similar attempts elsewhere could enhance the performance of farm women from small and marginal farms in their roles as agricultural producers leading to increased productivity, income and food security.